An improved soil ionization representation to numerical simulation of impulsive grounding systems - Gazzana, Daniel S.; Tronchoni, Alex B.; Leborgne, Roberto C.; Bretas, Arturo S.; Thomas, Dave W. P.; Christopoulos, Christos (Institute of Electrical and Electronics Engineers, 2018)
This paper presents a hybrid method based on the transmission line modeling method (TLM) aiming to represent the soil ionization effect for grounding systems simulation. This natural phenomenon can be better represented by taking into account the variation of the conductive components present in the TLM circuit and considering the residual resistivity remaining in the soil. The proposed analytical formulation is developed with a focus on the computational implementation of the method. The model is validated by comparing synthetized test results with measured data and other numerical models (residual resistivity, TLM, and analytical model). High precision together with an easy to implement formulation indicates that the methodology presents potential for real-life applications.